Photogrammetry and deformation of tubular connections - Tan, Heng Hai. (2010)
This report looks into the accuracy of photogrammetry in determining the deformation of tubular joints under the influence of loads as well as heat. In addition, it also looks into the various areas whereby photogrammetry can be applied and the relevance of it in the application.